Seasonal Movements and Distribution of Steller’s Eiders (Polysticta stelleri) Wintering at Kodiak Island, Alaska - Rosenberg, Daniel H.; Petrula, Michael J.; Schamber, Jason L.; Zwiefelhofer, Denny; Hollmén, Tuula E.; Hill, Douglas D. (ARCTIC, 2014)
We used satellite telemetry in 2004–06 to describe the annual movements and habitat use of a segment of the Pacific population of Steller’s Eiders (Polysticta stelleri) that winters at Kodiak Island, Alaska. Information about broad-scale patterns of seasonal distribution and links among annual cycle stages is critical for interpreting population trends and developing conservation strategies. We captured birds in Chiniak Bay at Kodiak Island in late February and early March and monitored the movements after departure from Kodiak Island of 24 satellite-tagged birds: 16 after-second-year (ASY) age class females, one second-year age class female, and seven ASY males. All birds used the same intercontinental migration corridor during spring, but routes and chronology of spring migration appeared to vary by year and among individuals. Sixteen of the 24 birds that were tracked migrated to breeding areas along the Arctic coast of Russia from the Chukotka Peninsula to the Taymyr Peninsula; five birds, assumed to be non-breeding, spent the summer in nearshore waters of Russia and Alaska; and the remaining three birds either died during spring migration or had failed transmitters. Thirteen birds were tracked to molt sites that were broadly distributed along the coast of Alaska. Molt sites included St. Lawrence Island, the Kuskokwim Shoals, Kamishak Bay, and three sites along the Alaska Peninsula. Twelve of these 13 birds returned to Kodiak Island to winter, and a single male wintered on the Alaska Peninsula. Steller’s Eiders marked during winter at Kodiak Island were widely distributed during the breeding season, but a large proportion of marked birds returned to molting and wintering areas in two years of the study. De 2004 à 2006, nous avons recouru à la télémétrie satellitaire pour décrire l’utilisation de l’habitat et les mouvements annuels d’un segment de la population d’eiders de Steller (Polysticta stelleri) dans la région du Pacifique, eiders qui hivernent sur l’île Kodiak, en Alaska. Il est essentiel d’obtenir ...